Changing temporal trends in non-AIDS cancer mortality among people diagnosed with AIDS: San Francisco, California, 1996–2013. (February 2018) - Hessol, Nancy A.; Ma, Danning; Scheer, Susan; Hsu, Ling C.; Schwarcz, Sandra K.
Highlights: From 1996–2013 there has been a shift in the cancer burden among people with HIV. The proportion of cancer deaths significantly decreased for AIDS-defining cancers. The proportion of cancer deaths significantly increased for non-AIDS cancers. Mortality rates for anal, liver, lung/larynx, and rectal cancer remained elevated. Anal, liver, and lung/larynx cancer are targets for prevention and screening. Abstract: Background: Antiretroviral therapy (ART) has reduced AIDS-defining cancer (ADC) mortality, but its effect on non-AIDS-defining cancer (NADC) mortality is unclear. To help inform cancer prevention and screening, we evaluated trends in NADC mortality among people with AIDS (PWA) in the ART era. Methods: This retrospective cohort study analyzed AIDS surveillance data, including causes of death from death certificates, for PWA in San Francisco who died in 1996–2013. Proportional mortality ratios (PMRs), and year, age, race, sex-adjusted standardized mortality ratios (SMRs) were calculated for 1996–1999, 2000–2005, and 2006–2013, corresponding to advances in ART. Results: The study included 5822 deceased PWA of whom 90% were male and 68% were aged 35–54 at time of death. Over time, the PMRs significantly decreased for ADCs (2.6%, 1.4%, 1.2%) and increased for NADCs (4.3%, 7.0%, 12.3%). For all years combined (1996–2013) and compared to the California population, significantly elevated SMRs were observed for these cancers: all NADCs combined (2.1), anal (58.4), Hodgkin lymphoma (10.5), liver (5.2), lung/larynx (3.0), rectal (5.2), and tongue (4.7). Over time, the SMRs for liver cancer (SMR 19.8, 11.2, 5.0) significantly decreased while the SMRs remained significantly elevated over population levels for anal (SMR 123, 48.2, 45.5), liver (SMR 19.8, 11.2, 5.0), and lung/larynx cancer (SMR 5.3, 4.7, 3.6). Conclusion: A decline in ADC PMRs and increase in NADC PMRs represent a shift in the cancer burden, likely due to ART use. Moreover, given their elevated SMRs, anal, liver, and lung/larynx cancer remain targets for improved cancer prevention, screening, and treatment.